Identifying Top School Indicators in Education Transition Document - Entezari, Monir sadat; Sharifi, Asgar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The purpose of this study was to identify the characteristics of the top school in the document of education transition. The research method was objective-fundamental and qualitative in terms of data type. The statistical population of the study consisted of the managers and staff of the Ministry of Education, the provincial administrations and the educational districts. Sample size in the qualitative section was determined by theoretical saturation principle of 23 people who were selected by purposeful sampling. In the present study, semi-structured interview tool was used for data collection. The validity and reliability of both instruments were confirmed. Data analysis was done by coding method. The results showed that the factors that constituted the top school in the transition document balance included moral, social, economic, political, bio / physical and scientific education and technology; Management, educational space and equipment, information technology, as internal and Islamic community requirements, media, family, educational justice, were external requirements.